Sorção, dessorção e seleção de espécies vegetais para remediação de solo contaminado com ametryn - Cortez, Alanna Oliveira (Universidade Federal Rural do Semi-Árido, 2017)
The knowledge of the factors related to the dynamics of herbicides in the environment it’s fundamental importance to predict the behavior of herbicides in soils with different attributes and to the selection of suitable dosages, and to avoid detrimental effects on the environment and on subsequent crops. The use of plants can aid in the remediation of the contaminated soil, and the herbicide tolerance is an essential factor for the species used. The objective of this work was to evaluate the sorption and desorption for a better understanding of soil ametryn behavior and to select plant species for remediation programs in areas contaminated with the herbicide. In the determination of sorption and desorption, the “Batch Equilibrium” method was used to determine the equilibrium time of ametryn in eleven soils with different attributes. In the sorption test the ametryn solutions (0, 1, 2, 4, 8, 16, 24 and 32 mg L-1) prepared in CaCl2 0,01 mol L-1 were added 10mL to samples of 200g of soil, shaken for 4 hours. The Desorption was evaluated using tubes containing a concentration of 16 mg L-1 before the sorption test, to which were added 10 mL of the solution of CaCl2 0,01 mol L-1 without herbicide. All the supernatants were filtered and the concentration of the herbicide analyzed by high performance liquid chromatography. The selection of ametryn tolerant species was performed by means of two experiments. In the first one the tolerance of the twenty seven species was evaluated to half of the recommended dose of the herbicide (1.000 g ia ha-1). In the second experiment, the selected ones were submitted to three different doses of the herbicide (0, 1000 e 2000 g i.a ha-1). The results showed that the sorption was higher in soils with high organic matter content and higher ion exchange capacity.The ametryn caused the death of Leucaena leucocephala, Crotalaria juncea, Crotalaria ochoroleuca, Fagopyrum tataricum, Mimosa caesalpiniaefolia, Arachis pintoi, Crotalaria spectabilis, Pennisetum glaucum, Glycine max, Calopogonium mucunoides, Mucuna pruriens, Vigna unguiculata, Phaseolus vulgaris, Sesamum indicum e Gossypium hirsutum. Canavalia ensioformis was tolerant until to dose 1000 g i.a ha-1 of ametryn. Cajanus cajan and Brachiaria decumbens until to dose 2000 g i.a ha-1 and present potential for inclusion in the remediation program of this herbicide
Sorption, desorption and selection of vegetable species for of soil remedies contaminated with ametryn
Keywords: Persistência; Carryover; Contaminação ambiental; Persistence; Carryover; Environmental contamination; MULTIDISCIPLINAR::CIENCIAS AMBIENTAIS::AMBIENTE, TECNOLOGIA E SOCIEDADE